2020
DOI: 10.1002/aorn.13277
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Perioperative Nursing Shortage Via a Perioperative Nursing Preceptorship for Baccalaureate Nursing Students

Abstract: A growing demand for perioperative nurses, insufficient interest in the perioperative nursing specialty, and nurse retirements have resulted in a perioperative nursing workforce shortage. Undergraduate nursing students’ limited exposure to perioperative content, along with facility hiring practices that exclude recently graduated nurses, further contribute to this shortage. To address these concerns, a large health care system in the midwestern United States partnered with a college of nursing to institute a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Of note, students felt strongly that their communication and teamwork skills increased as did their confidence in their ability to perform nursing tasks independently (Table 3). The lowest‐scoring skill development area was in pharmacology, which aligns with the findings from other perioperative nursing preceptor and student survey results 16 …”
Section: Survey Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Of note, students felt strongly that their communication and teamwork skills increased as did their confidence in their ability to perform nursing tasks independently (Table 3). The lowest‐scoring skill development area was in pharmacology, which aligns with the findings from other perioperative nursing preceptor and student survey results 16 …”
Section: Survey Resultssupporting
confidence: 84%
“…The lowestscoring skill development area was in pharmacology, which aligns with the findings from other perioperative nursing preceptor and student survey results. 16 Survey respondents indicated that the resources and clinical experiences for their OR placement supported their overall experience in the program (Table 4). Specifically, both students and preceptors found that implementation of hands-on laboratories where students developed basic skills before they entered the OR environment was beneficial (Table 5), although two (22%) of the students noted that the laboratory on prepping and draping was not as helpful because the surgeons performed these tasks at the facility where they were placed.…”
Section: 63mentioning
confidence: 99%
“…The purpose of this study was to examine nursing career choices after graduation among individuals who completed a perioperative elective. Twenty‐five (38%) of the 65 participants who completed the perioperative elective entered the field after graduation, a finding that aligns with the literature indicating that exposure of nursing students to the field of perioperative nursing during their undergraduate studies may well contribute to their entry into the specialty 5‐12,16,27,31,32 . The situation variable 25 prevailed in the qualitative comments, but a case also can be made for its effect on the quantitative findings because of the variety of situations readily available to the students that exposed them to perioperative practice.…”
Section: Discussionsupporting
confidence: 60%
“…Factors contributing to the current perioperative nursing shortage consist of academic concerns and issues associated with work environments. Academic factors in undergraduate nursing programs include a lack of specialty education (eg, didactic and clinical exposure to perioperative nursing), 5‐10 a lack of perioperative nurse faculty to teach content, 11 and the perception that the National Council Licensure Examination for Registered Nurses (NCLEX‐RN) does not include perioperative content and therefore it does not need to be included in the curriculum 12 …”
Section: Literature Reviewmentioning
confidence: 99%
“…e high blood glucose of diabetic patients with traumatic calcaneal fractures may retard fracture healing, and the patients are predisposed to postoperative complications such as incisional infections, which compromise the recovery of foot function and the quality of life of the patients [1][2][3]. It has been suggested that the combination of perioperative targeted therapeutic interventions contributes to reducing postoperative complications and shortening the recovery time [4,5]. To this end, this study was conducted to assess the efficacy of targeted treatment in the perioperative management of diabetic patients with traumatic calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%